Evaluasi Website Repositori Institusi Universitas Surabaya - Amirul Ulum (Pustakaloka, 2015)
The  development  of  institutional  repositories  (IRs)  in Indonesia within the broader framework of open access has significant impact on preserving intellectual capital and scholarly communication. Institutional  repositories  play  a  fundamental  role  in  centralizing, preserving,  and  making  accessible  institution’s  intellectual  capital. Evaluation of the system is to determine the functionality the system to meet the users need. Using a descriptive analysis this study wants to evaluate institutional repositories of University of Surabaya. The result is usefull for institution to develop the repository systems.